2022
DOI: 10.54127/qrco6765
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depressive, Anxiety, and OCD Symptoms among University Students in Singapore During COVID19

Abstract: Using self-report screening questionnaires, this study surveyed 1779 university students twice in 2021 to estimate the prevalence of depressive, anxiety, and OCD symptoms across a six-month period during the COVID-19 pandemic in Singapore. Across two waves of measurement, results showed that the prevalence of elevated depressive and anxiety symptoms were 29-34% and 25%, respectively. The prevalence of those who met the screening criteria of OCD was 5.7-7.1%. These estimates appeared to be consistent with other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In a study among 2,031 American university students, 38.5% reported a moderate-to-severe level of anxiety, and 48.1% had a moderate-to-severe level of depression ( Wang et al, 2020 ). In Singapore, according to a survey of 1,779 university students, the prevalence of depression and anxiety symptoms was high at 32 and 25%, respectively ( Yong and Keh, 2022 ). Besides, the present study found a particularly high prevalence of Internet addiction (around 78%).…”
Section: Discussionmentioning
confidence: 99%
“…In a study among 2,031 American university students, 38.5% reported a moderate-to-severe level of anxiety, and 48.1% had a moderate-to-severe level of depression ( Wang et al, 2020 ). In Singapore, according to a survey of 1,779 university students, the prevalence of depression and anxiety symptoms was high at 32 and 25%, respectively ( Yong and Keh, 2022 ). Besides, the present study found a particularly high prevalence of Internet addiction (around 78%).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a survey of 3,881 college students in mainland China reported an anxiety rate of 26.6% and a depression rate of 21.2% under the pandemic ( Chang et al, 2020 ). Similarly, in Singapore, the rates of anxiety and depression in college students during the pandemic reached 25 and 32%, respectively ( Yong and Keh, 2022 ). In the United States, a study of 2,031 college students under the pandemic found a prevalence of depression and anxiety, respectively, at 48.1 and 38.5% ( Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%